2021
DOI: 10.7554/elife.59629
|View full text |Cite
|
Sign up to set email alerts
|

Use of signals of positive and negative selection to distinguish cancer genes and passenger genes

Abstract: A major goal of cancer genomics is to identify all genes that play critical roles in carcinogenesis. Most approaches focused on genes positively selected for mutations that drive carcinogenesis and neglected the role of negative selection. Some studies have actually concluded that negative selection has no role in cancer evolution. We have re-examined the role of negative selection in tumor evolution through the analysis of the patterns of somatic mutations affecting the coding sequences of human genes. Our an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 321 publications
2
29
0
Order By: Relevance
“…Interestingly, previous studies suggest that there is some selection pressure in these comorbidities (body mass index [82], chronic kidney disease [83], diabetes [84], altered LDL/HDL/triglyceride levels [74,85], coronary artery disease/ischemic heart disease [86], hypertension [87], hyperuricemia [74], osteoporosis [88], and prostate cancer [89]) related to gout [74]. Accordingly, in the following section we focus on examples of mechanistic investigations of the regulatory elements of TFBSs related to transcription factors, affected genes, and disease phenotypes in gout and its associated comorbidities which exhibit selection signatures in susceptibility loci.…”
Section: Consequences Of Tfbs Genetic Variants: Disease Susceptibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, previous studies suggest that there is some selection pressure in these comorbidities (body mass index [82], chronic kidney disease [83], diabetes [84], altered LDL/HDL/triglyceride levels [74,85], coronary artery disease/ischemic heart disease [86], hypertension [87], hyperuricemia [74], osteoporosis [88], and prostate cancer [89]) related to gout [74]. Accordingly, in the following section we focus on examples of mechanistic investigations of the regulatory elements of TFBSs related to transcription factors, affected genes, and disease phenotypes in gout and its associated comorbidities which exhibit selection signatures in susceptibility loci.…”
Section: Consequences Of Tfbs Genetic Variants: Disease Susceptibilitymentioning
confidence: 99%
“…Gout is associated with prostate cancer [81], and prostate cancer risk genes display the signature of selection pressure [89]. Several studies have also identified the transcription factor and downstream effector genes involved with the prostate cancer-associated TFBS variant.…”
Section: Prostate Cancermentioning
confidence: 99%
“…Tumorigenesis mainly depends on the activation of oncogenes and the inactivation of tumor suppressor genes [ 4 ]. Most of these proto-oncogenes and tumor suppressor genes play an important role in regulating the cell cycle progression, and dysregulation of these genes contributes to cancer progression [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tumorigenesis mainly depends on the activation of oncogenes and the inactivation of tumor suppressor genes [ 4 ]. Most of these proto-oncogenes and tumor suppressor genes play an important role in regulating the cell cycle progression, and dysregulation of these genes contributes to cancer progression [ 4 ]. PLK1 (Polo-like kinase 1) is a member of the polo-like kinase family of serine/threonine protein kinases and plays an important role in regulating the cell cycle.…”
Section: Introductionmentioning
confidence: 99%
“…The overall conclusion of de Magalhães (conveyed by the title of his paper) is that “every gene can (and possibly will) be associated with cancer” and that “if a gene has not been associated with cancer yet, it probably means it has not been studied enough and will most likely be associated with cancer in the future” [ 1 ]. The author is correct in pointing out that this conclusion would have important implications for analyzing and interpreting large-scale analyses in cancer genomics, especially as it contradicts the dominant view that cancer is driven by a few hundred cancer genes, whereas the vast majority of genes are just bystanders (or passengers) in carcinogenesis (ICGC/TCGA Pan-Cancer Analysis of Whole Genomes Consortium, 2020; [ 2 , 3 , 4 ]).…”
Section: Introductionmentioning
confidence: 99%